Evaluación de la dinámica poblacional de Spodoptera frugiperda, Diatraea saccharalis y Dalbulus maidis en el cultivo de maíz (Zea mays L.) durante la época seca en cinco localidades del Cantón Mocache. - Burgos Macías, Tyron Jonathan (2020)
The study of the population dynamics of insects is important since it allows to identify fluctuations, occurrence of insects, as well as the factors and mechanisms that regulate them. The objective of this research was to evaluate the population dynamics of Spodoptera frugiperda, Diatraea saccharalis and Dalbulus maidis in the cultivation of corn (Zea mays L.) during the dry season in five locations in the Mocache canton. The investigation was carried out in: Pechiche, Barro Colorado, Jesús del Gran Poder, Las Campanas and Las Palmas. Light traps and yellow adhesive traps were placed, making weekly infestation records, specimens captures, as well as identification of beneficial insects. According to the results obtained in Barro Colorado, the increase in S. frugiperda infestation depends 82.81% on the increase in temperature, while in the town of Pechiche an increase in relative humidity conditions a 75.69% decrease in infestation of said insect. S. frugiperda affected the crops between week 3 and 9 of age, while D. maidis and D. saccharalis showed incidence until the end of the crop, beginning their occurrence from week 2 and 4, respectively. The light traps allowed capturing between 66 to 80 specimens of S. frugiperda and 74 to 160 D. saccharalis, while the adhesive traps recorded captures between 1580 and 3556 specimens of D. maidis during the period of the culture cycle. In the study area, different beneficial insects were found for the biocontrol of S. frugiperda, D. saccharalis and D. maidis, among which Telenomus spp., Euplectrus sp. and Zelus leucogrammus. Keywords: Pest monitoring, corn cultivation, integrated pest management